A Novel Heat Sink Design and Prototyping for LED Desk Lamps. (11th October 2015) - Chu, Li-Ming; Chang, Wei-Chin; Huang, Ting Hsuan
Abstract : Light-emitting diode (LED) is a modern lighting device. If the heat dissipating mechanism of LED desk lamp is not well designed, the induced high temperature will cause the reduction of illumination and life time of lamp. Therefore, the heat sink design becomes a key technology for LED lighting device. This study developed a methodology to design and analyze a heat sink for LED cooling. Four different types of heat sinks with fins in longitudinal or transverse directions and with or without vents on the base plate were compared. By using the CFD software FLUENT, heat flux and temperature around the heat sink were analyzed, and the surface temperature distribution was also investigated. The simulation outcomes were compared with experiments results to verify analysis accuracy. The comparisons show only slight differences, and the deviations were less than 4.0%. For cooling LED desk lamp, the design of using 12 vents on both sides of heat sink through natural convection to create the chimney effect was adopted; consequently, the temperature dropped 5°C in average. This design can also reduce the material of heat sink, LED lamp weight, and production cost.